Methodology for assessing the capital of a construction organisation for the project implementation - Kapusto, Anna V.; Kostjukova, Svetlana N.; Pashkevich, Nadezhda A. (Journal of the Belarusian State University. Economics, 2022)
A methodology for assessing the capital of a construction organisation when choosing a project is presented. It is based on an assessment of the adequacy of equity capital to perform construction and installation work under a new contract, the need and possibility of attracting borrowed capital based on the established payment schedule under the contracts. The methodology makes it possible to model the process of raising equity and debt capital, determine the feasibility of concluding a new contract, taking into account the fulfilment of obligations under existing contracts, and also develop strategies for regulating the contractor’s cash flows that provide a reserve of borrowed capital for concluding new contracts.
Keywords: construction; contractor; customer; capital; assessment; methodology